An Evaluation of the Program‐Specific Paragraph in the Otolaryngology Residency Application. (24th September 2018) - Stepan, Katelyn O.; Kaul, Vivian F.; Raquib, Aaishah R.; Kozin, Elliott D.; Sethi, Rosh K.; Malkin, Benjamin D.; Gray, Stacey T.; Teng, Marita S.
Abstract : Objectives/Hypothesis: The recent addition of mandatory program‐specific paragraphs within the personal statement during the otolaryngology match process has been controversial. It is unclear whether applicants customize these paragraphs for programs, or if they are largely uniform across applications. The objective of our study was to assess the degree of variability among program‐specific paragraphs. Study Design: Retrospective cohort analysis. Methods: An analysis of deidentified program‐specific paragraphs of 2016 otolaryngology residency applicants at two institutions was performed. Applicants who applied to both and had program‐specific paragraphs were included. Paragraphs were assessed for 24 parameters, including quantitative content analysis. Subjective and objective similarity scores were assigned to each pair, using a five‐point scale and Levenshtein distance function respectively. Differences between institutions were calculated using χ 2 and two‐sided t tests. Results: Two hundred eight‐five applications were reviewed, and 181 applied to both programs and had program‐specific paragraphs. The median subjective similarity score among all paragraphs was "mildly similar" (2/5). The mean objective similarity score was 0.59. There were statistical differences between institutions in 13 parameters. One institution garnered more applicants who mentioned interest in research or global surgery (71.3% vs. 57.5%, P  = .006; 17.7% vs. 4.4%, P  < .0001, respectively), whereas the other attracted mention of clinical aspects and geographical ties (80.0% vs. 45.3%, P  < .0001; 72.4% vs. 45.3%, P  < .0001, respectively). Conclusions: Our study suggests that applicants tailor program‐specific paragraphs to the individual residency programs. These findings may aid programs and students in understanding the role of this new element of the application. Level of Evidence: 4 Laryngoscope, 2508–2513, 2018